The implementation issue in norm diffusion: the cases of WTO anti-dumping duty and countervailing duty in China - Zhao, Yujia (2016)
China increasingly integrates into the international system, but has the social capitalist China been effectively contained by the Western-led liberal order? Most current literatures assume China’s ratification of international treaties as the signal to its full adoption of international norms, and scholars such as John Ikenberry thus argue that China is getting contained by the Western liberal order. However, a new wave of norm diffusion scholars suggests that even the ratified norms may not have the expected domestic impacts; the implementation process is decisive to the real changes ‘on the ground’. Following this vein, this thesis studies China’s implementation of international liberal norms in order to understand how the liberal world contains China in its order.